THE EFFECT OF SINGLE LEG DEPTH JUMP AND QUICK LEAP EXERCISE ON THE RESULTS OF INCREASING LEAD MUSCLE POWER AND LONG JUMP RESULTS IN WOMEN ATHLETES CLUB ATHLETIC NORTH FIELD IN 2022 - Nabilah Nakita; Mahmuddin Mahmuddin (Journal Physical Education, Health and Recreation, 2022)
AbstractThe purpose of this study was to determine the effect of single leg depth jump and quick leap exercises on the results of increasing leg muscle power and long jump results in female athletes at the North Medan Athletic Club in 2022. This study was an experimental study. The data collection technique in this study used a standing broad jump test and a long jump test using the prefix . The subjects of this study were 6 female long jump athletes. Selected by using total sampling technique . This research was conducted in the field of the North Medan Athletic Club. The data analysis technique used inferential statistics with a t-test at a significant level of 0.05. The results of the research on the single leg depth jump and quick jump exercise hypotheses obtained t-count standing broad jump ( 3.62) > t table (2.57) and t-count long jump (5.55) > t-table (2, 57). These results can be concluded that the single leg depth jump and quick jump exercises have a significant effect on the results of increasing leg muscle power and long jump ability in female athletes at the North Medan Athletic Club in 2022 .